(untitled) (Bangladesh Journal of Botany, 2021)
The feasibility of mixing fly ash to sandy soil to build the artificial plow pan of paddy soil in the Yellow River beach was explored. Water infiltration characteristics, saturated hydraulic conductivity, saturated water content and water storage capacity of the artificial plow pan were measured by using laboratory column tests. The results showed that under the same bulk density, when the amount of fly ash increased, the movement rate of the plow pan wetting front, the infiltration rate and the saturated hydraulic conductivity were decreased, then the water content and water storage of the soil layer increased. When the application amount of the fly ash was the same, and when the compaction weight decreased, the wetting front movement rate and saturated hydraulic conductivity increased and the soil water content and water storage capacity decreased. Mixing of fly ash with sand at a ratio of 1:3 (by weight) was found to be ideal for making an artificial of plow pan having bulk density of 1.7 g/cm3. Bangladesh J. Bot. 50(3): 993-1002, 2021 (September) Special